The Bio-Adsorption Pattern Bacteria Symbiont Sponge Marine Against Contaminants Chromium and Manganese In The Waste Modification of Laboratory Scale - Marzuki, Ismail (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2020)
The use of sponge symbionts bacteria as marine biomaterials in the heavy metal bio-adsorption method is an effort to save the marine environment from contamination of heavy metal contaminants. The ocean is a giant container, most vulnerable to contamination of pollutants. The target of the research is to determine the potential, capacity and pattern of bio-adsorption of sponge symbionts bacteria against various pollutants so that the toxic properties of heavy metal contaminants can be minimize. The method used is to interact with the bacterial suspension on the test metal concentrations that have been determined. The parameters measured were optical density, pH and concentration of heavy metals after the interaction lasted several days and the calculation of capacity, efficiency and bio-adsorption patterns of bacterial isolates from sponges. Results: The pattern and bio-adsorption power of AC bacteria to Cr and Mn ions were higher than AC bacteria, the adaptability of AC and BS bacteria was stronger in Cr (III) contaminated media compared to Cr (VI) toxic media, causing bacterial cell population BS and AC in Cr (III) and Mn (II) media are more abundant than in Cr (VI) and Mn (VII) media, capacity and bio-adsorption efficiency of BS and AC bacteria agains Cr (III) ˃ Cr (VI) ions and Mn (II) ˃ Mn (VII), It is suspected that there is an influence of reactivity and toxic properties of the metal ion test on the performance of the sponge symbionts in bio-adsorption